ORGANIZATIONAL AND METHODOLOGICAL BASIS OF EDUCATIONAL DISCIPLINES "PHYSICAL EDUCATION" FOR OF STUDENTS OF PEDAGOGICAL UNIVERSITIES - Andrianov, V.Ye.; Pysmenny О.М.; Andrianov, T.V. (Pedagogy of Higher and Secondary Education, 2006)
The article deals wile the problem of student’s preparation of practice at school as physical training teachers. Different sports exercises and games are described here.